ANALISIS TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN BAHASA ARAB DI MTs-NU Al-ISLAMIYAH ASEMBAGUS MENURUT TEORI MC CLELLAD - Akhsan Akhsan; Ahmadi Muhammadiyah (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
This reserch aims to determine the students' motivation in learning Arabic at MTs-NU Al-Islamiyah Asembagus and to determine the inhibiting and supporting factors that make students motivated or not motivated to learn Arabic. The problem formulation that has been determined is then analyzed using McClelland's theory. The type of this research is a qualitative research with the research subjects 8 students of class VIII and 8 students of IX. Data collection techniques using interviews, observation, and documentation. Data analysis was carried out using qualitative descriptive. The data obtained came from Arabic teachers and students of grades VIII and IX. The results showed that: 1) The majority of students at MTs-NU Al-Islamiyah Asembagus do not yet have the motivation to learn Arabic. 2) Based on McClelland's theory, it shows that students who have motivation to learn Arabic do not really pursue achievement with high rankings, the majority of students like competition.